Odpowiedzi

2010-03-20T18:20:08+01:00
35x-18+43=2x+15+23x
35x-2x-23x =15+18-43
10x = -10 /:10
x= -1

3y-7+4-6y-13+3y=5y-4+18-2y
3y-6y+3y-5y+3y= -4+18+7-4+13
-2y = 38 /(-2)
y= -19

pozdrawiam;)
Najlepsza Odpowiedź!
2010-03-20T18:24:34+01:00
35x-18+43 = 2x+15+23x
35x+25 = 25x+15
35x-25x = 15-25
10x = -10 |:10
x = -1

sprawdzenie:
L = 35*(-1)-18+43
L = -35+25
L = -10
P = 2*(-1)+15+23*(-1)
P = -2+15-23
P = 13-23
P = -10
L = P


3y-7+4-6y-13+3y = 5y-4+18-2y
-16 = 3y+14
3y = -16-14
3y = -30 |:3
y = -10

sprawdzenie:
L = 3*(-10)-7+4-6*(-10)-13+3*(-10)
L = -30-7+4+60-13-30
L = -33+17
L = -16
P = 5*(-10)-4+18-2*(-10)
P = -50-4+18+20
P = -54+38
P = -16
L = P